Muscle Regenerative Capacity May Be Reduced When Aerobic Exercise Is Initiated with Low Glycogen Content. (29th May 2020) - Margolis, Lee; Wilson, Marques; Whitney, Claire; Carrigan, Christopher; Murphy, Nancy; Hatch-McChesney, Adrienne; Pasiakos, Stefan
Abstract: Objectives: Maintaining low muscle glycogen content during recovery from aerobic exercise with low carbohydrate, high fat feeding has been shown to reduce insulin-mediated anabolic signaling compared to high carbohydrate feeding. The effects of low muscle glycogen content on intracellular regulators of muscle mass before and after aerobic exercise with carbohydrate ingestion is unclear. This study examined the effect of initiating aerobic exercise with low muscle glycogen content on postprandial insulin-dependent muscle anabolic signaling and myogenesis. Methods: Twelve men (mean ± SD, age: 21 ± 4 y; body mass: 83 ± 11 kg; VO2peak : 44 ± 3 mL/kg/min) completed 2 cycle ergometry glycogen depletion trials separated by 7 d, followed by a 24-h period of isocaloric high fat (1.5 g/kg carbohydrate, 3.0 g/kg fat) or high carbohydrate (6.0 g/kg carbohydrate, 1.0 g/kg fat) refeeding to elicit low (LOW; 217 ± 103 mmol/kg dry wt) or adequate (AD; 396 ± 70 mmol/kg dry wt) glycogen content in randomized order. Participants then performed 80 min of cycle ergometry (64 ± 3% VO2peak ) while ingesting 146 g of carbohydrate. Protein signaling (Western blotting) and gene transcription (RT-qPCR) were determined from vastus lateralis biopsies obtained before glycogen depletion (baseline, BASE), and before (PRE) and after (POST) exercise. Data presented as fold change relative to BASE for LOW and AD. Results: Independent of time, carbohydrate sensing p-AMPK Thr172 was higher ( P < 0.05) in LOW compared to AD, while p-p38MAPK Thr180/Tyr182 was higher ( P < 0.05) in LOW at POST, but not different PRE. Insulin sensitive p-AKT Thr473 was higher ( P < 0.05) in AD compared to LOW, regardless of time. Anabolic regulators, p-mTORC1 Ser2448, p-p70S6K Ser424/421, and p-rpS6 Ser235/236 were higher ( P < 0.05) POST compared to PRE and BASE, independent of group. Regulators of myogenesis, MYOD and MYOGENIN were lower ( P < 0.05) in LOW compared to AD, regardless of time, while PAX7 was lower ( P < 0.05) in LOW compared to AD at PRE, but not different POST. Conclusions: Initiating aerobic exercise with low muscle glycogen content does not appear to affect downstream insulin-dependent anabolic signaling, yet reductions in myogenic regulator factors suggest muscle repair and remodeling in recovery from exercise may be impaired. Funding Sources: Work supported by DHP JPC-5/MOMRP; authors' views not official U.S. Army or DoD policy.